Solvent assisted catalytic conversion of beech wood and organosolv lignin over NiMo/γ-Al2O3. Issue 4 (30th January 2020) - Parto, Soheila Ghafarnejad; Jørgensen, Emma Kathrine; Christensen, Jakob Munkholt; Pedersen, Lars Saaby; Larsen, Daniel Bo; Duus, Jens Øllgaard; Jensen, Anker Degn
Abstract : Lignin in biomass is degraded to a handful of chemicals in the presence of a NiMo/Al2 O3 catalyst and ethanol medium. Abstract : Beech wood was directly converted into lignin derived monomers and dimers and holocellulose derived light hydrocarbons in the presence of a sulfided NiMo/γ-Al2 O3 catalyst in ethanol medium at 200 to 300 °C. The reaction products were carefully analyzed with techniques such as gas chromatography mass spectrometry equipped with a flame ionization detector (GC-MS-FID), size exclusion chromatography (SEC), elemental analysis and heteronuclear single quantum coherence nuclear magnetic resonance (HSQC NMR). The main identified monomers obtained at 300 °C were 4-propyl guaiacol (PG) and 4-propyl syringol (PS) with a total monomer yield of 18.1 wt% based on the Klason lignin content in beech wood. At a lower reaction temperature of 200 °C, the process targets only the lignin with a monomer yield of 12.1 wt% based on the Klason lignin content, while the holocellulose is conserved and can be used for a subsequent fermentation or hydrocracking process. The highest monomer yield of 20.0 wt% based on the Klason lignin content was obtained at 260 °C, indicating that the optimum temperature required for degradation of lignin fractions to monomers is within 200–260 °C. The direct conversion of biomass with high yield of lignin monomers showed promise compared to a two-step process involving initial isolation of lignin by the organosolv method and subsequent conversion of organosolv lignin. Here, a monomer yield of only 4.3 wt% was detected at 300 °C. Moreover, the oil from the direct biomass conversion possessed a lower molecular weight compared to the oil from the organosolv lignin conversion.